2021
DOI: 10.1002/pmrj.12518
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review of Metatarsal Bone Stress Injury in Athletic Populations: Etiology, Biomechanics, and Management

Abstract: Metatarsal bone stress injuries (BSIs) are common in athletic populations. BSIs are overuse injuries that result from an accumulation of microdamage that exceeds bone remodeling. Risk for metatarsal BSI is multifactorial and includes factors related to anatomy, biology, and biomechanics. In this article, anatomic factors including foot type, metatarsal length, bone density, bone geometry, and intrinsic muscle strength, which each influence how the foot responds to load, are discussed. Biologic factors such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 112 publications
0
7
0
Order By: Relevance
“…Furthermore, one of the reasons for the occurrence of overuse injuries is suboptimal running technique, resulting in poor lower limb kinematics [ 29 , 33 ], which results in the uneven distribution of forces between body segments. It is suggested that one of the contributing factors to the development of running-related injuries may be the suboptimal lower limb kinematics, especially the inability to control the motion of the lower extremity segments in the frontal and transverse planes.…”
Section: Resistance Exercise For Modifying Running Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, one of the reasons for the occurrence of overuse injuries is suboptimal running technique, resulting in poor lower limb kinematics [ 29 , 33 ], which results in the uneven distribution of forces between body segments. It is suggested that one of the contributing factors to the development of running-related injuries may be the suboptimal lower limb kinematics, especially the inability to control the motion of the lower extremity segments in the frontal and transverse planes.…”
Section: Resistance Exercise For Modifying Running Techniquementioning
confidence: 99%
“…The majority of these injuries are overuse/chronic [ 27 ], with the highest incidence reported for iliotibial band syndrome (ITBS), patellofemoral pain syndrome (PFPS), Achilles tendinitis, plantar fasciitis, and medial tibial stress syndrome [ 28 ]. According to Troy et al [ 29 ], suboptimal biomechanics results in an uneven distribution of forces between body segments. This is seen particularly in people with PFPS and ITBS, where unevenly distributed forces increase stress on a particular part of a structure [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, ref. [13] reported metatarsal fatigue fractures to consist of 38% of all the bone stress injuries and even 58% in the military.…”
Section: Risk Of Fractures and Injuries In Sportsmentioning
confidence: 99%
“…For example, cavus foot could lead to SF of the femur and metatarsal bones, whereas flat foot increase pronation and SF of the tibia, the fibula, and the tarsal bones. Varus alignment in the lower limb increases SF risk of the femur and the tarsal bones, and cavovarus feet have a rigid foot shape that does not attenuate the impact and predisposes a person to SF (10,24). Athlete's triad or relative energy deficiency in sport (RED-S) is a known risk factor for SF.…”
Section: Intrinsic Factorsmentioning
confidence: 99%